Nitrogen‐Doped Ordered Mesoporous Carbon Supported Bimetallic PtCo Nanoparticles for Upgrading of Biophenolics. Issue 31 (13th June 2016) - Wang, Guang‐Hui; Cao, Zhengwen; Gu, Dong; Pfänder, Norbert; Swertz, Ann‐Christin; Spliethoff, Bernd; Bongard, Hans‐Josef; Weidenthaler, Claudia; Schmidt, Wolfgang; Rinaldi, Roberto; Schüth, Ferdi
Abstract: Hydrodeoxygenation (HDO) is an attractive route for the upgrading of bio‐oils produced from lignocellulose. Current catalysts require harsh conditions to effect HDO, decreasing the process efficiency in terms of energy and carbon balance. Herein we report a novel and facile method for synthesizing bimetallic PtCo nanoparticle catalysts (ca. 1.5 nm) highly dispersed in the framework of nitrogen‐doped ordered mesoporous carbon (NOMC) for this reaction. We demonstrate that NOMC with either 2D hexagonal ( p 6 m ) or 3D cubic ( Im 3 ‾ m ) structure can be easily synthesized by simply adjusting the polymerization temperature. We also demonstrate that PtCo/NOMC (metal loading: Pt 9.90 wt %; Co 3.31 wt %) is a highly effective catalyst for HDO of phenolic compounds and "real‐world" biomass‐derived phenolic streams. In the presence of PtCo/NOMC, full deoxygenation of phenolic compounds and a biomass‐derived phenolic stream is achieved under conditions of low severity. Abstract : The phenol cut : A novel method allows the synthesis of bimetallic PtCo nanoparticles (ca.1.5 nm) which are highly dispersed in the framework of nitrogen‐doped ordered mesoporous carbon (NOMC). The resulting PtCo‐NOMC shows high catalytic activity for hydrodeoxygenation of phenolic compounds and "real‐world" biomass‐derived phenolic streams.